2009
DOI: 10.1002/asna.200911240
|View full text |Cite
|
Sign up to set email alerts
|

Velocity curve analysis of the spectroscopic binary stars RZ Cas, CC Cas, HS Her, HD 93917, V921 Her and Y Cygni by the artificial neural networks

Abstract: We use an Artificial Neural Network (ANN) to derive the orbital parameters of spectroscopic binary stars. Using measured radial velocity data of six double-lined spectroscopic binary systems RZ Cas, CC Cas, HS Her, HD 93917, V921 Her and Y Cygni, we find corresponding orbital and spectroscopic elements. Our numerical results are in good agreement with those obtained by others using more traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…They redetermined the mass ratio of the binary system to be = 0.244 and set the effective temperature of the primary star to be 1 = 7700 K. Their results concluded that V921 Her was a shallow contact binary system. However, Karami and Mohebi [5] and Karami et al [6] also obtained the mass ratio of V921 Her, both of which were consistent with those determined by Rucinski et al [3].…”
Section: Introductionsupporting
confidence: 87%
“…They redetermined the mass ratio of the binary system to be = 0.244 and set the effective temperature of the primary star to be 1 = 7700 K. Their results concluded that V921 Her was a shallow contact binary system. However, Karami and Mohebi [5] and Karami et al [6] also obtained the mass ratio of V921 Her, both of which were consistent with those determined by Rucinski et al [3].…”
Section: Introductionsupporting
confidence: 87%
“…The star has also been observed by Hipparcos and new UBV observations were secured during the 1999 observing campaign in Hvar, Korea, and with the Four College APT in Arizona. Hvar observations continued in 2006and 2009. In 2006, two eclipses in BVR were observed by PS.…”
Section: Photometrymentioning
confidence: 81%
“…Comparing the disentangled and synthetic spectra, they obtained a new estimate of the T eff and log g for both components. New orbital elements of Y Cyg were derived from the published radial velocities (RVs) of by Karami & Teimoorinia (2007), who used a least-squares technique, and by Karami et al (2009), who used the artificial neural network method and who arrived at virtually identical masses for both stars.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations